Isolation of endophytic bacteria from nutmeg plant as antibacterial agents against pathogenic bacteria - Melda Yunita; Yosephina Manse; Myllisa Citra Wulandari; Sukmawati Sukmawati; Morgan Ohiwal (JPBIO (Jurnal Pendidikan Biologi), 2022)
Recently, exploration of natural antibiotic alternatives by utilizing medicinal plants is often carried out. Nutmeg plant (Myristica fragrans Houtt) is a tropical plant endemic to the Maluku Island and often used as medicine by local people. This study was aimed to isolate endophytic bacteria from the nutmeg plant and detect its potential as an antibacterial against pathogenic bacteria. The study is a descriptive observational study with a true experimental approach. Endophytic bacteria were isolated from several organs of the nutmeg plant such as leaves, leaf bones, stems, fruit flesh, and seeds and then tested for their inhibition against Staphylococcus aureus, Propionibacterium acne, and Escherichia coli. The results showed that: (1) the highest total population of endophytic bacteria was found in the seeds of nutmeg (7.5x104 CFU/ml), (2) ten isolates of endophytic bacteria were obtained with varying morphological characteristics, and (3) the detection of antibacterial activity showed that of the 10 isolates obtained, 4 isolates were able to inhibit the growth of Escherichia coli, namely isolate BEAD2, BEATD1, BEABJ 2, and BEABJ 1 with the diameter of the inhibition zones of each isolate being 3.4 mm, 3.2 mm, 1.6 mm and 1.5 mm respectively. The conclusion of this study is that 4 isolates of endophytic bacteria were detected as potential antibacterial against Escherichia coli.